A CASE REPORT OF MODERATE COVID-19 AND MALARIA FALCIPARUM CO-INFECTION WITH THROMBOCYTOPENIA - Nelda Aprilia Salim; Harun Hudari; Mega Permata; Yenny Dian Andayani; Zen Ahmad; Verdiansah Verdiansah (JURNAL KEDOKTERAN DAN KESEHATAN, 2021)
The COVID-19 pandemic that attacks the world has made the attention of all medical personnel focused on this disease. The clinical picture is similar to other infectious diseases such as malaria, dengue, influenza, etc., which often leads to misdiagnosis. We report the case of a man, 31 years old, with a history of travel and complaints of high fever persisting for more than 7 days. On physical examination, the temperature was 39-40 C, others were within normal limits. Initial platelet count was 69 x 103/µL, leukocytes was 15.52 x 109/L, CRP was 96 mg/L. The blood smear found Plasmodium falciparum, and PCR SARS-CoV-2 was positive. Chest X-ray showed pneumonia. Dihydroartemisinin-piperaquine and primaquine therapies were administered for malaria, as well as favipiravir, azithromycin, and other symptomatic therapy for COVID-19. Platelets decreased to 38 x 103/µL while D-dimer level increased (> 20 mg/L). Anticoagulant was delayed. On monitoring after therapy, the platelets returned to normal, the D-dimer level decreased, and there was no bleeding. The co-infectious conditions of malaria and COVID-19 should be suspected in patients with suggestive symptoms and travel history from endemic areas, therefore both examinations should be performed. This co-infection has the potential to cause hyper inflammation and hypercoagulation and this is associated with a poor prognosis. Appropriate treatment is needed.